Kreowanie niebiznesowych i-społeczności - Watras, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Beside business communities, there are also other societies that are not related to business. The main reasons to set up these communities, among others, are: common interests, hobbies, convictions, opinions, needs and also demographic and culture features. This article presents the process of creating non-business communities with special attention to particular criteria. E-communities are also presented by Maslow's theory of needs. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 469-477